Advances in Computational Multibody Systems - Ambrósio, Jorge A.C (Computational Methods in Applied Sciences, 2005)
Among all the fields in solid mechanics the methodologies associated to multibody dynamics are probably those that provide a better framework to aggregate different disciplines. This idea is clearly reflected in the multidisciplinary applications in biomechanics that use multibody dynamics to describe the motion of the biological entities, or in finite elements where the multibody dynamics provides powerful tools to describe large motion and kinematic restrictions between system components, or in system control for which multibody dynamics are the prime form of describing the systems under analysis, or even in applications with fluid-structures interaction or aeroelasticity. This book contains revised and enlarged versions of selected communications presented at the ECCOMAS Thematic Conference in Multibody Dynamics 2003 that took place in Lisbon, Portugal, which have been enhanced in their self-containment and tutorial aspects by the authors. The result is a comprehensive text that constitutes a valuable reference for researchers and design engineers and helps to appraise the potential of application of multibody dynamics to a wide range of scientific and engineering areas of relevance.